Reconstructing the Concept of Khilāfah through Muhammad Abed al-Jabiri's Bayānī and Burhānī Epistemology: Insights for Contemporary Indonesia - Muhammad Hafizh; Muhammad Rifqi Zam Zami; Dini Pepilina; Mohamad Fauzan (Balai Diklat Keagamaan Bandung, 2026)
The resurgence of khilāfah discourse in Indonesia has intensified debates over the legitimacy of political authority in Islam, with several movements advocating the establishment of a universal caliphate as a religious obligation. While existing studies have examined this discourse from political, ideological, and historical perspectives, limited attention has been devoted to the epistemological assumptions underlying scriptural interpretations of khilāfah. Addressing this gap, this study reinterprets the concept of khilāfah through Muhammad Abed al-Jabiri’s epistemological framework by integrating the Bayānī (textual) and Burhānī (rational) modes of reasoning. Using qualitative library research with a descriptive-analytical approach, the study examines Qur'anic verses, classical Arabic lexical sources, al-Jabiri’s epistemological writings, and relevant contemporary scholarship. The analysis combines textual interpretation with rational inquiry informed by the objectives of Islamic law (maqāṣid al-sharīʿah). The findings demonstrate that the Qur'anic verses commonly invoked to justify a universal caliphate do not prescribe a single normative model of political governance. From a Bayānī perspective, khilāfah primarily denotes succession, stewardship, and accountable leadership, whereas the Burhānī approach situates political authority within the principles of justice, public welfare, social harmony, and the protection of fundamental human interests. This study contributes to the literature by offering an epistemological reinterpretation that challenges literalist readings of khilāfah and argues that claims regarding the religious obligation of a universal caliphate require contextual, linguistic, historical, and maqāṣid-oriented reasoning. The proposed framework provides a more inclusive and contextually relevant understanding of Islamic governance in contemporary Indonesia.